Gingivitis & Dental Caries Status among the School Going Children of Jamshoro City (Medical Forum Monthly, 2024)
ABSTRACTObjective: The purpose of the study is to assess the gingivitis and dental caries status among school going children of Jamshoro city.Study Design: Descriptive StudyPlace and Duration of Study: This study was conducted at the out patients department of Liaquat University Hospital Jamshoro during the year Jan 2010 to Oct 2011Materials and Methods: A descriptive study was conducted among 700 school going children. The general information and the information regarding oral hygiene practice and dental visits were obtained. The gingivitis of the subjects was assessed by using Loe and Silness Gingival Index. The dental caries status was assessed by using International Caries Detection and Assessment System.Results: Out of 700 school children, n=270 (38.57%) were boys and reaiming n=430 (61.42%) were girls, the age distrubution was done in three groups and in group one total children were n=101 (14.42%), in group two n=187 (26.71%) and in group three n=432 (58.85%) children, Gingival Index according to Loe and Silness in grade zero were n=322 (46.00%) childern, grade one n=165 (23.57%) children, grade two n=143 (20.42%) children and in grade three n=70 (7%) children, Dental Caries Status of school children in relation with age group was in age group one n=199 (28.42%) children, in age group two n=175 (25%) children and in age group three n=115 (16.42%) children.Conclusion: The results of this study indicate that there is a moderate prevalence of gingivitis and dental caries among school going children of jamshoro city. We the dental care providers, oral hygienist, parents and teachers trying to motivate the school going childrens for to improving the oral health of the oral cavity so that they can prevent themselves from common problems of the oral caivty.